Cadmium affects microtubule organization and post-translational modifications of tubulin in seedlings of soybean (Glycine max L.) - Gzyl, Jarosław; Chmielowska-Bąk, Jagna; Przymusiński, Roman; Gwóźdź, Edward A. (Frontiers in Plant Science, 2015)
Cadmium is a non-essential heavy metal, toxic to all living organisms. The microtubule (MT) cytoskeleton appears to be one of the main targets of cadmium action. In this study we present, with the use of a various immunological approaches, the effect of cadmium at moderate (85 micromolar) and high (170 micromolar) concentrations on the structure and functioning of the MT cytoskeleton in the root cells of soybean seedlings. As the result of heavy metal action, root growth was significantly diminished and was accompanied by a reduction in mitotic activity and disturbance in the structure of the MT arrays, including randomization of the cortical MT arrangement, distorted mitotic arrays and complete depolymerization of the MTs. Biochemical analysis revealed decreased levels of various alpha- and beta-tubulin isoforms with a parallel down-regulation of most examined alpha-tubulin genes. Simultaneously, cadmium treatment led to differentiated changes in the level of tubulin post-translational modifications, including tyrosination, detyrosination, acetylation and polyglutamylation. Decreased tyrosination and polyglutamylation of particular tubulin isoforms accompanied by increase in the level of specific detyrosinated and acetylated isoforms implies augmented stability and reduced turnover of the MTs during stress conditions. Taken together, the obtained results indicate the significant impact of cadmium on gene expression levels and subsequent post-translational processing of tubulin, which may be related to the impairment of microtubule cytoskeleton functioning in root cells.